Conflict and Cooperation in Labour-Management Relations. A Comparative Approach: Canada-Poland - Wratny, Jerzy (Revue générale de droit, 1994)
Until 1980, labour relations in Poland were entirely run by the state. As a result of massive strikes and social negotiations the first independent trade union “Solidarność” was established. The 1989 elections, which lead to the defeat of the Communist government, finally opened the door for legal reform of the Polish industrial relations model. In this article, the author examines the evolution and development of the Polish labour relations system in contrast with the situation and latest trends of labour negotiations in Canada, a democratic country with a market economy.